Autogenous Transplantation for Replacing a Hopeless Tooth - Zakershahrak, Mehrsa; Moshari, Amirabbas; Vatanpour, Mehdi; Khalilak, Zohreh; Jalali Ara, Afsoon (Iranian Endodontic Journal, 2016)
Autogenous tooth transplantation (ATT) is a simple and reasonable choice for replacing the missing teeth when a proper donor tooth is available. This report presents a case of successful ATT of a maxillary right third molar for replacement of mandibular right second molar with a concomitant endodontic-periodontal disease. The mandibular second molar was believed to be hopeless due to a severe damage to coronal tooth structure, inappropriate root canal treatment and apical radiolucency. After extraction of mandibular second molar and maxillary third molar (the donor), the tooth was re-implanted into the extracted socket of second molar site. Root canal therapy was then performed. After 3 years, clinical and radiographic examinations revealed satisfying results, with no signs and symptoms. The patient is asymptomatic and the transplanted tooth is still functional with no signs of marginal periodontal pathosis. Radiographies showed bone regeneration in the site of previous extensive periapical lesion, normal periodontal ligament with no signs of root resorption. Keywords: Autogenous; Auto-Transplantation; Endodontic; Surgical Procedure; Third Molar